Tafenoquine: A 2018 Novel FDA-Approved Prodrug for the Radical Cure of Plasmodium vivax Malaria and Prophylaxis of Malaria - Annie Mayence; Jean Jacques Vanden Eynde (MDPI AG, 2019)
Tafenoquine (an 8-aminoquinoline) was approved by the Food and Drug Administration (FDA) in 2018 for the radical cure of Plasmodium vivax malaria and preventive action against malaria. Despite the fact that the mechanism of action of the drug remains unclear, all studies indicated that a metabolite is responsible for its efficacy. Routes for the preparation of the drug are described.